Theoretical and experimental investigation for developing a gas-liquid two-phase flow meter. (March 2022) - Monachan, Binet; Thomas, Rijo Jacob; Skaria, Mathew; Shafi, K.A.; Emmanuel, B.; Kasthurirengan, S.; Sahu, A.K.; Dave, Haresh
Abstract: Despite the intricacy, inline metering of two-phase flow has a significant impact in multitudinous applications including fusion reactors, oil, nuclear, and other cryogenic systems. Since measurement of individual flow rate is prominent in various systems, it warrants the establishment of a flow meter system that can monitor the mass flow rates of liquid. In this regard, an approach was taken towards the development of a two-phase flow meter system in the present study. The concept involves two-phase flow through narrow parallel rectangular channels resulting in laminar, stratified flow with a slope at the liquid-vapor interface. The height of the liquid column at specific channel locations is measured for determining the flow rate. However, the geometric configurations of the channels and fluid properties are pivotal in ensuring accurate measurement. Consequently, theoretical and experimental studies are performed to investigate the correspondence between flow rate and change in liquid height. Based on the governing equations, a theoretical model is established using MATLAB®. The model investigated the intricate influence of various flow and fluid properties in the estimation of the mass flow rate. The experimental investigation was done with various conditions under different liquid and vapor volume flow rates for validating the proposed supposition and the theoretical model. Both the theoretical and experimental analyses showed fair correspondence. The proposed system estimated the mass flow rate within a tolerance of ±10% and showed potential towards the development of the cryogenic two-phase flow meter. Highlights: Mathematical model provided an insight into the influence of fluid and geometrical parameters on the measurement method. Established the correlation between mass flow rate and slope developed. Increasing the length of the channel results in higher pressure drop, however would help in accurate measurement. Width of the channel dictate flow characteristics and slope at the interface. Concept of estimating mass flow rate from slope is proved a potential candidate for cryogenic two-phase flow meter.